(untitled) (Revista Apotheke, 2024)
This article contributes to the fields of Visual Arts Education and Special Education, specifically focusing on the education of blind and visually impaired individuals. By revisiting the historical contexts of Art Education in Brazil, we mapped out a thought process and exploration of ways to facilitate experimental creative processes within two disciplines of a Technical Crafts Course – Proeja, offered by an institution specialized in the education of visually impaired individuals. These processes were made possible by the clues found in the course syllabi and were put into practice through the research-creation method. In this manner, contributions emerge from the rhizomatic notes of these experiments, which constitute evolving worlds with each experience and life made possible by the lessons. Rhizomatic notes do not contain within themselves the possibilities of experimentation in the field of teaching, but are presented as triggers to continue creating paths and ways to make Visual Arts Education more accessible.